Manajemen Praoperatif pada Pasien Emergensi dengan Perdarahan Internal - Adiyanto, Bowo; Pratomo, Bhirowo Yudo; Sarjono, Pramuditya Haryo (Jurnal Komplikasi Anestesi, 2021)
Bleeding is one of the most common cases that will be encountered by an anesthesiologist. Patients with internal bleeding have a high mortality rate and tend to detoriate quickly. The patient should get immediate and proper treatment. Preoperative management from an anesthesiologist has important role to the outcome of the patients. Management of patients with internal bleeding should be based on recent studies. Damage Controlled Resuscitation (DCR) and permissive hypotension is now the recommended concept of managing bleeding patients. Further studies should be conducted for the best management of patients.